2017
DOI: 10.1042/bsr20170676
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells can be applied to red blood cells storage as a kind of cellular additive

Abstract: During storage in blood banks, red blood cells (RBCs) undergo the mechanical and metabolic damage, which may lead to the diminished capacity to deliver oxygen. At high altitude regions, the above-mentioned damage may get worse. Thus, more attention should be paid to preserve RBCs when these components need transfer from plain to plateau regions. Recently, we found that mesenchymal stromal cells (MSCs) could rescue from anemia, and MSCs have been demonstrated in hematopoietic stem cells (HSCs) transplantation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…We also found that high-dose CLV-100 infusion provided a significant increase in both hemoglobin level and MCV level that falls within the normal range. Another study indicated that MSCs maintained a better quality of hemoglobin as well as the oxygen-carrying capacity [ 27 ] as more hemoglobin helps in controlling the level of nitric oxide, thus expanding the blood vessels for more blood flow. Hemoglobin is also important for immunity where free hemoglobin serves as an alarm molecule that signals bleeding and tissue damage, which drives macrophage production towards a protective, antioxidative macrophage type, that halts lesion progression at later stages of disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that high-dose CLV-100 infusion provided a significant increase in both hemoglobin level and MCV level that falls within the normal range. Another study indicated that MSCs maintained a better quality of hemoglobin as well as the oxygen-carrying capacity [ 27 ] as more hemoglobin helps in controlling the level of nitric oxide, thus expanding the blood vessels for more blood flow. Hemoglobin is also important for immunity where free hemoglobin serves as an alarm molecule that signals bleeding and tissue damage, which drives macrophage production towards a protective, antioxidative macrophage type, that halts lesion progression at later stages of disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…RBCs may be stored up to 35 days before transfusion according to Chinese standards and up to 42 days according to US and EU standards [20,21,22]. Although there are evidences reporting the potential harm of transfusing stored RBCs [1,2,3,4,5,6,7,8,9,10,11], other studies on randomized clinical trials reported no difference in mortality of patients who received fresher versus older RBCs [23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, according to these evidences, it is still difficult to evaluate the positive or negative clinical impact of using stored RBCs on patients [22,27,28]. Actually, stored RBCs undergo slow deleterious changes over time during storage, decreasing their viability at 24 h post-transfusion to 70% in the 35 days stored RBCs [29], although these stored RBCs still meet the storage level accepted by several countries [20,21,22]. Despite more attention is now being paid to the storage damage found in banked RBCs, further studies are needed to increase our knowledge on RBC storage modifications to evaluate their potential consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, several culture systems have been established to obtain a sufficient number of mature and functional RBCs in vitro [ 8 ]. Three culture systems including erythroid cells lines (the murine erythroleukemia cell line and the human K562 cell line), HSCs derived from peripheral blood (PB) and UCB, and stem cells (human ESCs, neonatal cord blood (CB), mesenchymal stem cells (MSCs), and human iPSCs) have been evaluated to obtain RBCs [ 26 , 45 ]. An immortalized or continuous cell lines have a homogenous karyotype that can be altered following continuous cell culture, which might not be the most appropriate for pre-clinical studies or clinical applications [ 46 ].…”
Section: Introductionmentioning
confidence: 99%